An exploration of health workers' experiences in providing bereavement care to mothers following a stillbirth: results from a subnational level health system in Uganda - Eric Ssegujja; Isaac Ddumba; Michelle Andipatin (BMC, 2023)
Abstract Background Stillbirth is a profound emotion-laden event to the mothers and health workers who provide care due to its sudden and unexpected occurrence. Health workers offering support in regions shouldering the highest-burden experience providing support to a stillbirth mother in their professional lifetime. However, their experiences seldom get documented as much of the focus is on mothers causing a dissonance between parental and clinical priorities. This study aimed to explore the health worker's experiences in the provision of bereavement care to mothers following a stillbirth. Methods An exploratory cross-sectional qualitative study was undertaken on a purposively selected sample of key informants drawn from frontline health workers and health systems managers providing maternal health services at a subnational level health system in Uganda. An interview guide was used to collect data with the audio-recorded interviews transcribed using Microsoft office word. Atlas. ti a qualitative data management software aided in coding with analysis following a thematic content analysis technique. Results There was no specialised bereavement care provided due to inadequate skills, knowledge of content, resources and support supervision for the same. However, health workers improvised within the available resources to comfort mothers upon news of a stillbirth. Disclosure to mothers about the stillbirth loss often took the form of forewarnings, direct and sometimes delayed disclosure. A feeling of unpreparedness to initiate the disclosure process to the mother was common while the whole experience had an emotional effect on the health workers when establishing the cause, particularly for cases without clear risk factors. The emotional breakdown was often a reflexive response from the mothers which equally affected the care providers. Health workers engaged in comforting and rebuilding the mothers to transition through the loss and validate the loss. Efforts to identify the skills and health systems gaps for address were a common response targeted at improving the quality of maternal healthcare services to avert similar occurrences in the future. Conclusion Providing care to mothers after stillbirth was an emotional and challenging experience for health workers requiring different approaches to disclosure and provision of emotional support. The aspect of specialised bereavement care was lacking within the current response. Reflection of unpreparedness to handle the tasks demonstrates a deficit in the required skills. It is a critical gap missing hence calling for dedicated efforts to address it. Targeting efforts to improve health workers' competencies and preparedness to manage grieving mothers is one way to approach it.